Kejadian Bullying Dengan Kualitas Tidur Remaja Pada Siswa MAN 1 Kota Kediri - DINI MAYA SAPUTRI; Linda Ishariani; Didit Damayanti (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Bullying is an unwanted action that occurs in adolescents, bullying incidents have the potential to occur repeatedly and at any time.  The impact of bullying incidents is the feeling of discomfort, fear, to the occurrence of sleep pattern disturbances in the victim. The aim of research was to determine the correlation between bullying incidence and adolescent sleep quality in students of MAN 1 Kediri city. The design of this research used correlation with cross-sectional approach, with purposive sampling technique, obtained a sample of 63 respondents from 220 populations. Data collection for this research used a questionnaire and PSQI (Pittsburgh Sleep Quality Index), followed by analysis used the Spearmen's Rank test. The results showed that the incidence of bullying in students of MAN 1 Kediri City was almost entirely (77.8%), namely 49 respondents experienced a moderate level of bullying, while the sleep quality of adolescents in MAN 1 Kediri City students was mostly (55.6%), namely 35 respondents had poor sleep quality. Analysis of the Spearmen's Rank test data (p-value 0.017 <0.05) showed that there was a correalation between the incidence of bullying and adolescent sleep quality in students of MAN 1 Kediri city with the category of moderate relationship closeness (r = 0.300). The bullying that students get is verbal and psychological bullying such as being called an inappropriate name, getting body shaming, feeling ostracized. It is better for adolescent to increase their knowledge about the incidence of bullying starting from the factors, criteria, until the impact occurs due to bullying so that adolescent can improve their attitude in combating bullying behavior and reduce the incidence of bullying.